Pedagogical Conditions of Adaptive Physical Training of Injured Military Servants - Shynkaruk, Viktor (Pedagogical Discourse, 2024)
The article is devoted to the analysis of the experience and practical examples of adaptive physical training of the military, in particular, wounded during combat operations. The relevance of the problem of adaptive physical training is due not only to the significant number of wounded military personnel, but also to the need to create effective methods that allow restoring not only physical, but also psychological resources of the individual. Existing approaches to physical rehabilitation are largely focused on the general principles of rehabilitation, however, adaptation to specific injuries and wounds requires individualized and comprehensive programs. Military injuries can vary from minor injuries to serious injuries, such as loss of a limb, spinal cord injury, traumatic brain injury, which require not only medical, but also pedagogical efforts to restore their physical capabilities. Methodological approaches to the organization of adaptive physical training should be based on the principles of individualization and progressiveness. Selection and correction of exercises for different categories of wounded is the basis for creating effective rehabilitation programs. An important condition is to take into account the type of injury, physical capabilities and psychological state of the soldier. Successful adaptive physical training programs in Ukraine and abroad are considered, which contribute to the restoration of physical capabilities and improvement of the psychological state of military personnel. The impact of such programs on functional recovery, as well as the positive effect of psychological rehabilitation for the military, are described. The responses of rehabilitation program participants were analyzed and the problems and prospects for the development of adaptive physical training were identified. The importance of integrating innovative technologies, new methods, and a multidisciplinary approach to create effective adaptation and rehabilitation programs was emphasized. The main problems, such as shortcomings in existing programs and resource limitations, were identified that need to be taken into account to improve adaptive physical training for the military.